2015
DOI: 10.1016/j.matdes.2015.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic wood-based biomorphic Sr3Co2Fe24O41 Z-type hexaferrite ecoceramics made from cork templates

Abstract: Ecoceramics (environmentally conscious ceramics) are biomimetic/biomorphic ceramics, which use a naturally occurring and sustainable material as a template for their unique morphology and structure. Usually woods (or lignocellulosics) are used, due to the inherent cellular nature of their microstructures. The wood is pyrolised and the resulting carbon skeleton impregnated with a fluid, and this is then heated to combust the carbon template and convert the fluid precursor into a ceramic, while maintaining the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 25 publications
1
16
2
Order By: Relevance
“…SEM images showed that the cellular structure of the cork was maintained, with hexagonal cells around 20-30 μm in diameter, and cell walls <1 μm thick. Unlike the large grained hexaferrite ecoceramics made from cork reported previously by Pullar et al [26], the individual grains of these CeO2 ecoceramics were on the nanoscale size range, being no more than 100 nm in diameter. Another important feature was that, while the rectangular side walls were maintained to hold the cellular cork structure, the rear hexagonal walls were pierced, with these holes repeating through the structure.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…SEM images showed that the cellular structure of the cork was maintained, with hexagonal cells around 20-30 μm in diameter, and cell walls <1 μm thick. Unlike the large grained hexaferrite ecoceramics made from cork reported previously by Pullar et al [26], the individual grains of these CeO2 ecoceramics were on the nanoscale size range, being no more than 100 nm in diameter. Another important feature was that, while the rectangular side walls were maintained to hold the cellular cork structure, the rear hexagonal walls were pierced, with these holes repeating through the structure.…”
Section: Discussioncontrasting
confidence: 66%
“…The first biomorphic ceramics produced were of "SiC wood" [21] from charcoal, and since 1998 several types of pyrolised wood were used as templates to create SiC "ceramic wood" [22,23], as well as oxide ceramics such as CeO2 [24,25]. Many different soft and hard woods have been use as pyrolised templates for Ecoceramics, but cork was never used, despite its obvious suitability, until the pioneering work by Pullar et al [26], although this use was previously referred as a possible future trend [12]. Pullar et al created the first ever cork-based Ecoceramics, in the form of magnetic hexagonal ferrite ceramic foams, with the cellular structure of cork.…”
Section: Introduction*mentioning
confidence: 99%
“…Pullar et al have carried out innovative work to create biomorphic ecoceramics of ferrites and ceria from cork templates (Pullar et al, 2015, 2016; Pullar and Novais, 2017). Cork naturally has similar dimensions to the pine-derived ecoceramic above, yet with a more regular 3-DOM (three-dimensionally ordered macroporous) microstructure.…”
Section: Biomimetic Porous Ceria From Natural Templatesmentioning
confidence: 99%
“…Adsorption is a well‐known equilibrium separation process and an effective method for water decontamination. A variety of adsorbents such as activated carbon , biomass , graphene oxide , natural mineral material , and waste materials have been used to deal with the wastewater. Among these adsorbents, activated carbon is the most commonly used adsorbent for the removal of heavy metals from wastewater.…”
Section: Introductionmentioning
confidence: 99%